The Survival of the Hessian Nobility, 1770-1870 - Pedlow, Gregory W., 1949- (Book collections on Project MUSE., 1988)
Here is a broad and richly documented examination of a little studied social group--the German nobility outside Prussia. Gregory Pedlow considers the nobles of the small but representative state of Hesse-Kassel from the end of the ancien regime to the era of German unification. Although this period has been most often described in terms of the "triumph of the bourgeoisie," the author shows that landholding Hessian nobles were able to preserve much of their political prestige and social and economic power during these years. By demonstrating a mixture of conservatism and flexibility instead of blind reaction, the Hessian nobility maintained its position as a landed elite.The author focuses on four main areas: the noble family, with material showing changes in marriage patterns and family size and the impact of such demographic changes on inheritance practices; noble landownership, with documentation as to how noble landholdings and landed income survived the loss of traditional noble privileges and payments by peasants; noble occupations, with information (including collective biography) showing nobles' education, career choices, and degree of success in obtaining positions in government service; and the nobility's political response to the growing pressure for reform during the nineteenth century.Originally published in 1988.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.